EXPLORING SYNONYMY IN SOME WILD ANIMAL NAMES IN THE UZBEK LANGUAGE - Khidirova Makhfuza Amirkulovna (Western European Studies, 2024)
This article analyzes the synonyms in wild animal names in the Uzbek language. The phenomenon of synonymy reflects the diversity of the Uzbek language’s vocabulary, revealing regional and dialectal peculiarities in the naming of animals. The study explores the synonymy of wild animal names, examining the range of usage, semantic differences, and their regional characteristics. This work contributes to a deeper understanding of the synonymy of animal names and their role in the Uzbek language.
Keywords: wild animal names; synonymy; Uzbek language